2007
DOI: 10.1103/physrevb.75.195217
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic strain and phonon deformation potentials in GaN

Abstract: Nanoscience by an authorized administrator of DigitalCommons@University of Nebraska -Lincoln. Darakchieva, V.; Paskova, T.; Schubert, Mathias; Arwin, H.; Paskov, P.P.; Monemar, B.; Hommel, D.; Heuken, M.; Off, J.; Scholz, F.; Haskell, B.A.; Fini, P.T.; Speck, J.S.; and Nakamura, S., "Anisotropic strain and phonon deformation potentials in GaN" (2007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 45 publications
2
86
0
Order By: Relevance
“…28 These nucleation layers serve as templates for the growth of the nonpolar wurtzite film with unique epitaxial relationship with respect to the substrate. 21 On the other hand, the semipolar film is grown directly on the substrate without any nitridation ͑Table I͒. It has been previously shown that direct growth of InN on r-plane sapphire results in the nucleation of zinc-blende InN due to the much lower lattice mismatch compared to the wurtzite InN.…”
Section: Semipolar "101 1… Innmentioning
confidence: 99%
See 1 more Smart Citation
“…28 These nucleation layers serve as templates for the growth of the nonpolar wurtzite film with unique epitaxial relationship with respect to the substrate. 21 On the other hand, the semipolar film is grown directly on the substrate without any nitridation ͑Table I͒. It has been previously shown that direct growth of InN on r-plane sapphire results in the nucleation of zinc-blende InN due to the much lower lattice mismatch compared to the wurtzite InN.…”
Section: Semipolar "101 1… Innmentioning
confidence: 99%
“…20 The structural anisotropy of nonpolar III-nitride films affects their optical performance and device-relevant characteristics ͑carrier mobility, degradation, etc.͒, which requires detailed study of these issues. While the structural anisotropy of nonpolar GaN films have been extensively studied 1, [14][15][16][17][21][22][23] the information on the structural characteristics of nonpolar InN is very scarce 24,25 and detailed reports exists only for films grown on GaN substrates. 26,27 However, the nonpolar GaN substrates are not only extremely expensive but also have a limited supply.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 The uncoupled phonon mode parameters and the high-frequency limit of the dielectric function of GaN and InN are taken from our previous works. 40,42,43 The FCC contribution with consideration of longitudinal optical phonon plasmon coupling (LPP) was described by applying the Kukharskii model 29,44 e kð?Þ ðxÞ ¼ e 1;kð?…”
Section: Experimental and Data Analysismentioning
confidence: 99%
“…It can be easily implemented to work with uniaxial materials [45] (like corundum) and is sensitive to small anisotropies [46,47]. For our sample geometry, in which an oblique angle of incidence was used, only the ordinary dielectric function can be accessed with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%